2015
DOI: 10.1111/acem.12854
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the Broselow Tape in South Sudan, “The Hungriest Place on Earth”

Abstract: Objectives: The Broselow tape is a length-based tool used for the rapid estimation of pediatric weight and was developed to reduce dosage-related errors during emergencies. This study seeks to assess the accuracy of the Broselow tape and age-based formulas in predicting weights of South Sudanese children of varying nutritional status.Methods: This was a retrospective, cross-sectional study using data from existing acute malnutrition screening programs for children less than 5 years of age in South Sudan. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 30 publications
5
33
0
Order By: Relevance
“…Although the Broselow tape accurately estimated weight in children of average habitus (those with a TBW similar to IBW), it was critically inaccurate in underweight and overweight children and failed to estimate weight within 20% of actual weight in every obese child in this study. This has been frequently reported previously, with potentially dangerous overestimation of weight in low-and middle-income countries and substantial underestimation of weight in high-income populations [14][15][16][17][18]. The accuracy was highest in the youngest children, falling off significantly in children >25kg.…”
Section: Discussion the Performance Of The Weight Estimation Systems supporting
confidence: 77%
“…Although the Broselow tape accurately estimated weight in children of average habitus (those with a TBW similar to IBW), it was critically inaccurate in underweight and overweight children and failed to estimate weight within 20% of actual weight in every obese child in this study. This has been frequently reported previously, with potentially dangerous overestimation of weight in low-and middle-income countries and substantial underestimation of weight in high-income populations [14][15][16][17][18]. The accuracy was highest in the youngest children, falling off significantly in children >25kg.…”
Section: Discussion the Performance Of The Weight Estimation Systems supporting
confidence: 77%
“…[1] Estimated weights have been shown to be extremely inaccurate in many settings, however, with some studies in underweight and obese populations having shown weight estimations to be inaccurate in up to 85% of children. [2][3][4][5] These are dangerous results that would inevitably lead to many critical medication errors. Even in populations without extreme prevalences of underweight or obesity, many commonly used methods, such as age-based formulae, are frequently inaccurate in more than half the children in whom they are used.…”
Section: Researchmentioning
confidence: 99%
“…Using newer edition of the tape presumably creates a greater error in estimating the weight of our populations compared to prior edition as it has been modified to minimize weight underestimation in obese children in the USA. There are studies done in various parts of the world providing the adaptability and efficiency of the Broselow tape in measuring the weight of children [10,11,25] while other studies had contradictory conclusions [13][14][15][16][17]22]. Studies from Kenya [10] and South Africa [10,25] showed that the Broselow tape estimated weights varied only minimally from the actual weight.…”
Section: Discussionmentioning
confidence: 99%
“…In a simulated pediatric emergency, color coding significantly reduced the deviation from recommended doses [8]. The studies done in various parts of the world have shown that the Broselow tape accurately measured the weight of children [10][11][12] while some studies showed it to be inaccurate [13][14][15][16][17]. The scenario is quite different in low-income countries like Nepal [15,18,19].…”
Section: Introductionmentioning
confidence: 99%